Using the Google Places API and Google Trends Data to Develop High Frequency Indicators of Economic Activity - Austin, Paul.; Marini, Marco; Sanchez, Alberto; Simpson-Bell, Chima (Washington, D.C. : International Monetary Fund, 2021)
As the pandemic heigthened policymakers' demand for more frequent and timely indicators to assess economic activities, traditional data collection and compilation methods to produce official indicators are falling short-triggering stronger interest in real time data to provide early signals of turning points in economic activity. In this paper, we examine how data extracted from the Google Places API and Google Trends can be used to develop high frequency indicators aligned to the statistical concepts, classifications, and definitions used in producing official measures. The approach is illustrated by use of Google data-derived indicators that predict well the GDP trajectories of selected countries during the early stage of COVID-19. To this end, we developed a methodological toolkit for national compilers interested in using Google data to enhance the timeliness and frequency of economic indicators.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Environmental Accounts; Google Trends Data; Measurement and Data on National; Methodology for Collecting, Estimating, and Organizing Microeconomic Data; Reopening, COVID-19, High-Frequency Data and Business Register